2002
DOI: 10.1074/jbc.m207414200
|View full text |Cite
|
Sign up to set email alerts
|

Specific Activation of Human Interleukin-5 Depends on de Novo Synthesis of an AP-1 Complex

Abstract: It is clear from the biology of eosinophilia that a specific regulatory mechanism must exist. Because interleukin-5 (IL5) is the key regulatory cytokine, it follows that a gene-specific control of IL5 expression must exist that differs even from closely related cytokines such as IL4. Two features of IL5 induction make it unique compared with other cytokines; first, induction by cyclic adenosine monophosphate (cAMP), which inhibits other T-cell-derived cytokines, and second, sensitivity to protein synthesis inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…This can be explained by previous studies that demonstrated that other transcription factors, such as c-Maf, Stat 6, activator protein (AP-1), and nuclear factor activated T cell, cooperated with GATA-3 to regulate Th2 cytokine gene expression. 20,[32][33][34] Even though these transcriptional factors do not play a predominant role in Th2 gene expression, as they do with GATA-3, they still contribute partly to Th2 cytokines release.…”
Section: Discussionmentioning
confidence: 97%
“…This can be explained by previous studies that demonstrated that other transcription factors, such as c-Maf, Stat 6, activator protein (AP-1), and nuclear factor activated T cell, cooperated with GATA-3 to regulate Th2 cytokine gene expression. 20,[32][33][34] Even though these transcriptional factors do not play a predominant role in Th2 gene expression, as they do with GATA-3, they still contribute partly to Th2 cytokines release.…”
Section: Discussionmentioning
confidence: 97%
“…IL-5 promoter contains three responsive elements (RE) and a distal regulatory region, among which RE I (−80 bp to −45 bp) and RE II (−123 bp to −92 bp) regions are activating elements while RE III (−170 bp to −130 bp) and the distal regulatory region (−460 bp to −230 bp) are repressive elements [15,16]. A series of previous studies have demonstrated that several transcription factors, such as C/EBP␤, GATA3, NFAT, YY1, AP1 and Ets1, are able to bind onto these regions and significantly regulate IL-5 transcription [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 97%
“…This observation indicates that Fra-2 differentially regulates TRE-dependent gene expression, depending on the promoter context. Recently, Schwenger et al (30) have shown that a Fra-2-based AP1 complex is required for inducing human interleukin-5 gene transcription in T-cells. Both transient transfection and overexpression studies indicated a role for Jun-D in the up-regulation of fra-1 transcription, although EMSA and ChIP assays showed that Jun-D binds to the fra-1 promoter even in the absence of any stimulus (Figs.…”
Section: Fra-1 Regulation By Tumor Promotermentioning
confidence: 99%